Corrosion Behavior of Steel Sleeve Joint in Different Concentration of Sodium Chloride (NaCl) - Mohd Sohami, Umie Nadiatul Nadzirah; Mahmod, Muhammad Faisal (Journal of Advanced Mechanical Engineering Applications, 2022)
A steel sleeve joint is a common way to fix a pipeline that has corroded, however even this type of repair is not immune to corrosion. To understand and increase the effectiveness of the steel sleeve joint, the corrosion behavior of the steel sleeve joint in various sodium chloride concentrations has been examined in this study. Carbon steel sleeve joints in weld and pipe areas were examined using a Scanning Electron Microscope (SEM) and Energy Dispersive Spectroscopy (EDS), which were utilized to determine the surface morphologies and element composition. The sample’s parameters include sodium chloride concentrations of 15% and 33% and immersion times of 24, 48, and 72 hours. A Vickers hardness test is also done on the steel sleeve joint sample to compare the hardness of the weld and the pipe part. Results showed that the sample submerged in a 15% sodium chloride concentration corroded by more than 33%, and the corrosion product form increased with immersion time. The Vickers hardness number ranged from 216.4 to 284.8 HV for welds and 132.8 to 182.1 HV for pipe areas, respectively. The different values prove different corrosion behavior happen on both areas of the sample when compared by the results of surface morphologies and the Vickers hardness test.